Heart rate variability during epileptic seizures as a factor in the development of sudden unexpected death in epilepsy (literature review) - A. V. Monakhova; A. Yu. Yakshina; E. D. Belousova (Русский журнал детской неврологии)
Sudden unexpected death in epilepsy (SUDEP) is the most common cause of death in patients with epilepsy and occurs at least 20 times more often in patients with fore mentioned condition compared with healthy people. During epileptic seizures, a significant proportion of patients develop heart rate variability and respiratory depression. It is assumed that these cardiorespiratory complications are the most probable risk factor for the development of SUDEP. Asystole and ventricular fibrillation, developing immediately after the seizure, are the most significant arrhythmias in the pathophysiology of SUDEP. Discoordination of the autonomic nervous system activity in connection with the involvement of autonomous control centers in epileptic activity leads to the emerging cardiopulmonary pathology. In patients with long-term resistant epilepsy, chronic dysfunction of the autonomic nervous system is formed and, as a consequence, a greater predisposition to the disturbances of heart rhythm. A detailed study of cardiac disorders during epileptic seizures will provide the key for understanding the risks of developing SUDEP and developing some approaches to its prevention.